Toward Growing Robots: A Historical Evolution from Cellular to Plant-Inspired Robotics - Del Dottore, Emanuela; Sadeghi, Ali; Mondini, Alessio; Mattoli, Virgilio; Mazzolai, Barbara (Frontiers in Robotics and AI, 2018)
This paper provides the very first definition of “growing robots”: a category of robots that imitates biological growth by the incremental addition of material. Although this nomenclature is quite new, the concept of morphological evolution, which is behind growth, has been extensively addressed in engineering and robotics. In fact, the idea of reproducing processes that belong to living systems has always attracted scientists and engineers. The creation of systems that adapt reliably and effectively to the environment with their morphology and control would be beneficial for many different applications, including terrestrial and space exploration or the monitoring of disasters or dangerous environments. Different approaches have been proposed over the years for solving the morphological adaptation of artificial systems, e.g. self-assembly, self-reconfigurability, evolution of virtual creatures, plant-inspiration. This work reviews the main milestones in relation to growing robots, starting from the original concept of a self-replicating automaton to the achievements obtained by plant inspiration, which provided an alternative solution to the challenges of creating robots with self-building capabilities. A selection of robots representative of growth functioning is also discussed, grouped by the natural element used as model: molecule, cell or organism growth-inspired robots. Finally, the historical evolution of growing robots is outlined together with a discussion of the future challenges towards solutions that more faithfully can represent biological growth.